Private colleges in Malaysia: are the key marketing environment indicators promising? / Nooraini Mohamad Sheriff and Rozita Naina Mohamad - Mohamad Sheriff, Nooraini; Naina Mohamad, Rozita (Unit Penyelidikan dan Perundingan, 2003)
Private colleges have been long established in Malaysia since 1930's. Being the key sector of the private higher education market in Malaysia, private colleges have assumed great responsibilities in providing private higher education to Malaysians. Their concerted efforts have complemented al1d filled the vacuum left by the public higher educatiol1al institutions. Although private colleges have grown in leaps and bound, the dynamism displayed by its marketing environmental forces 11as been a cause for concern as they could pose as opportunity and threats. Henceforth there is a need for private colleges to understand the nature and magnitude of change plaguing these forces as well as the severity of their impact on operational and strategic activities. The main objective of this paper is to analyze the key marketing environmental forces surrounding the private higher educational market namely competition, legal and technology. An analysis of these forces has uncovered the presence of intense competition among private colleges in Malaysia. Two factors were identified as key sources of this competitive environment namely a large number of industry players (approximately 700) and homogeneity of courses offered. Competition too was present from a broader perspective that is internal, external and external territorial. As a result, the industry is currently face with saturation, thus making survival a priority. This has led to cost-cutting measures and sold outs especially by the small players. Additiol1ally competition too has compelled private colleges to enhance their present standard and hence giving customers an opportunity to choose their best option. Nevertheless, it was perceived that the private higher education industry is one that is not heavily regulated. However, the National Accreditation Board has played an active role to get private colleges to conform to their regulations. This has had some positive impact, namely improvements in the redressal system, feedback on students learning experience and a general enhancemel1t of quality and quantity across the industry. Technology Oil the other hand has been adopted in many facets of the education delivery process as well as administrative process of private colleges. However, working students tend to display a greater preference to this aspect of education. Technology compared to fresh school leavers. There are also cases where private colleges claimed to be on-line but their web sites are poorly maintained. Nevertheless, it is perceived that broad technological applications would propel the growth of private colleges and thus improving their prestige. Data for this exploratory research was collected from secondary sources and primary sources through in-depth interviews with middle to senior managers from established private colleges in the Klang Valley. Twenty private colleges in the Klang Valley were selected via simple random sampling using Wencom Higher Education Guide. However, only seven private colleges consented to participate. Fourteen middle managers were selected via judgment sampling to be interviewed. The researchers felt that only managers involved in strategy formulation would have a good understanding of the external environmental forces affecting their organization. In-depth interview was conducted at designated times with the use of a discussion guide to ensure a comprehensive coverage and smooth progress if each session. Findings were analyzed using the mechanical analysis method that allowed contradictions, majority and minority views to be reported.